(untitled) (Homoeopathy for All, 2023)
Thyroiditis is a general term for inflammation of the thyroid gland, and it can be associated with thyroid dysfunction. Thyroiditis is classified according to clinical symptoms (painful or painless), onset of symptoms (acute, subacute, chronic), and underlying etiology (autoimmunity, infection, drugs, radiation). The most common forms of thyroiditis include Hashimoto, postpartum, and subacute. Most forms of thyroiditis result in a triphasic disease pattern of thyroid dysfunction. Patients will have an initial phase of hyperthyroidism (thyrotoxicosis) attributed to the release of preformed thyroid hormone from damaged thyroid cells. This is followed by hypothyroidism, when the thyroid stores are depleted, and then eventual restoration of normal thyroid function. Some patients m a y d e v e l o p p e r m a n e n t hypothyroidism.